2011
DOI: 10.1097/ta.0b013e318216f611
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Mental Illness in a Trauma Center: Rooting Out a Risk Factor for Unintentional Injury

Abstract: This inpatient pilot screening program prospectively identified preexisting mental illness as a risk factor for unintentional injury. Implementation of validated psychosocial and mental health screening instruments is feasible and efficient in the acute trauma setting. Administration of a validated mental health screening instrument can be achieved by training college-level research assistants. This system of screening can lead to identification and treatment of mental illness as a strategy for unintentional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
3
25
0
1
Order By: Relevance
“…Those seeking medical care for unintentional injuries may be more likely to have unrecognised mental health needs that may have either contributed to or resulted from their injuries. Brief alcohol and substance abuse screening, intervention and referral programmes have been used successfully in trauma centres nationwide to prevent recurrent traumatic injury 39. Longitudinal research is needed to clarify causal relationships and identify mediators of the association between psychological distress and unintentional injury and also to evaluate the potential of mental health screening and intervention as an injury prevention strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Those seeking medical care for unintentional injuries may be more likely to have unrecognised mental health needs that may have either contributed to or resulted from their injuries. Brief alcohol and substance abuse screening, intervention and referral programmes have been used successfully in trauma centres nationwide to prevent recurrent traumatic injury 39. Longitudinal research is needed to clarify causal relationships and identify mediators of the association between psychological distress and unintentional injury and also to evaluate the potential of mental health screening and intervention as an injury prevention strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, studies from high-income countries (HICs) suggest that injured patients presenting to ECs may represent an at-risk group for mental disorders. A number of these studies have found that patients presenting with an injury were more likely to meet criteria for a pre-existing mental disorder than their non-injured counterparts (Dicker et al, 2011; O'Donnell et al, 2009; Poole et al, 1997; Wan et al, 2006). For example, a Canadian study found that patients hospitalized for injury were over nine times more likely to have been hospitalized for a mental disorder prior to the injury admission, and over three times more likely to have submitted mental health physician claims than the matched non-injured cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have looked at the impact of trauma on subsequent mental health, few studies have examined the impact of pre-existing mental health diagnoses on hospital resource use and cost after acute trauma. A study from San Francisco using medical records and registry data found similar rates of mental health diagnoses in cases of unintentional injury 16. These authors also found that patients with mental health diagnoses had longer lengths of stay and repeat admissions for injury 17…”
Section: Discussionmentioning
confidence: 94%